A preoperative simulation of medial open-wedge high tibial osteotomy for predicting postoperative realignment - Konda, Shoji; Ishibashi, Teruya; Tamaki, Masashi; Tomita, Tetsuya (Frontiers in Bioengineering and Biotechnology, 2023)
Three-dimensional preoperative surgical simulation of the medial open-wedge high tibial osteotomy (OWHTO), simplified as the rigid rotation around the hinge axis, has been performed to predict postoperative realignment. However, the practicality of this highly simplified simulation method has not been verified. This study aimed to investigate the validity of realignment simulation simplified as a rotation around a hinge axis compared with a postoperative CT model. A three-dimensional surface model of the tibia and femur was created from preoperative computed tomography (CT) images (preoperative model) of three patients. The simulation of medial OWHTO created sixty computer simulation models in each patient simplified as the rigid rotation of the proximal part of the tibia relative to the distal part from 1 degree to 20 degrees around three types of hinge axes. The simulation models were compared with the actual postoperative model created from postoperative CT images to assess the reality of the simulation model. The average surface distance between the two models was calculated as an index representing the similarity of the simulation model to the postoperative model. The minimum value of average surface distances between the simulation and postoperative CT models was almost 1 mm in each patient. The rotation angles at which the minimum value of average surface distances was represented were almost identical to the actual correction angles. We found that the posterior tibial tilt and the axial rotation of the proximal tibia of the simulation model well represented those of the postoperative CT model, as well as the valgus correction. Therefore, the realignment simulation of medial OWHTO can generate realistic candidates for postoperative realignment that includes the actual postoperative realignment, suggesting the efficacy of the preoperative simulation method.